Respuesta :

answer Y=1 over 4 and Y= 2 over 3 that is your answer and these are the steps I'm going to put a image hope this is useful to u and have a beuty day

Ver imagen Аноним
Ver imagen Аноним

Answer:

f(y) = 12y^2 -5y -2 = 0

a = 12 b =-5 c=-2

Using quadratic formula:

y = [-b +-sq root (b^2 -4ac)] / 2 a

y = [--5 +-sq root (25 -4*12*-2)] / 24

y = [5 +- sq root  (25 + 96) ] / 24

y = [5 +- sq root  (121) ] / 24

y = [5 + 11] / 24

y1 = (2/3) = .66666666666

y2 = 5 -11 / 24  

y2 = -(1/4) = -.25

Step-by-step explanation: